Synthesis, Characterization, and Biomedical Applications of a Targeted Dual-Modal Near-Infrared-II Fluorescence and Photoacoustic Imaging Nanoprobe - Cheng, Kai; Chen, Hao; Jenkins, Cesare H; Zhang, Guanglei; Zhao, Wei; Zhang, Zhe; Han, Fei; Fung, Jonathan; Yang, Meng; Jiang, Yuxin; Xing, Lei; Cheng, Zhen (ACS nano, 2017)
Our development of multifunctional dual-modal imaging probes aims to integrate the benefits from both second near-infrared (NIR-II) fluorescence (1000–1700 nm) and photoacoustic imaging with an ultimate goal of improving overall cancer diagnosis efficacy. Herein we designed a donor–acceptor chromophore based nanoparticle (DAP) as a dual-modal image contrast agent has strong absorption in the NIR-I window and a strong fluorescence emission peak in the NIR-II region. The dual-modal DAPs composed of D−π–A−π–D-type chromophores were PEGylated through nanoprecipitation. The multifunctional DAP surface was thus available for subsequent bioconjugation of EGFR Affibody (Ac-Cys-ZEGFR:1907) to target EGFR-positive cancers. The Affibody-conjugated DAPs appeared as highly monodisperse nanoparticles (∼30 nm) with strong absorption in the NIR-I window (at ca. 680 nm) and an extremely high fluorescence in the NIR-II region (maximum peak at 1000 nm). Consequently, the Affibody–DAPs show significantly enhanced photoacoustic and NIR-II fluorescence contrast effects in both in vitro and in vivo experiments. Moreover, the Affibody–DAPs have the capability to selectively target EGFR-positive tumors in an FTC-133 subcutaneous mouse model with relatively high photoacoustic and fluorescent signals. By taking advantage of high spatial resolution and excellent temporal resolution, photoacoustic/NIR-II fluorescence imaging with targeted dual-modal contrast agents allows us to specifically image and detect various cancers and diseases in an accurate manner.